Elite Haplotypes of a Protein Kinase Gene TaSnRK2.3 Associated with Important Agronomic Traits in Common Wheat - Miao, Lili; Mao, Xinguo; Wang, Jingyi; Liu, Zicheng; Zhang, Bin; Li, Weiyu; Chang, Xiaoping; Reynolds, Matthew; Wang, Zhenhua; Jing, Ruilian (Frontiers in Plant Science, 2017)
Plant specific protein kinase SnRK2s play crucial roles in response to various environmental stimuli. TaSnRK2.3, a SnRK2 member, was involved in the response to multiple abiotic stresses in wheat. To facilitate the use of TaSnRK2.3 in wheat breeding, the three genomic sequences of TaSnRK2.3, originating from the A, B, and D genomes of hexaploid wheat, were obtained. Sequence polymorphism assays showed four and ten variations were detected at TaSnRK2.3-1A and at TaSnRK2.3-1B, respectively, yet no variation was identified at TaSnRK2.3-1D. Three haplotypes for A genome, and two main haplotypes for B genome of TaSnRK2.3 were identified in 32 genotypes. Functional markers (2.3AM1, 2.3AM2, 2.3BM1, 2.3BM2) were successfully developed to distinguish different haplotypes. Association analysis was performed with the general linear model in TASSEL 2.1. The results showed that both TaSnRK2.3-1A and TaSnRK2.3-1B were significantly associated with plant height (PH), length of peduncle and penultimate node, as well as 1,000-grain weight (TGW) under different environments. Additionally, TaSnRK2.3-1B was significantly associated with stem water-soluble carbohydrates at flowering and mid-grain filling stages. Hap-1A-1 had higher TGW and lower PH; Hap-1B-1 had higher TGW and stem water-soluble carbohydrates, as well as lower PH, thus the two haplotypes were considered as elite haplotypes. Geographic distribution and allelic frequencies indicated that the two preferred haplotypes Hap-1A-1 and Hap-1B-1 were positively selected in the process of Chinese wheat breeding. These results could be highly valuable for genetic improvement and germplasm enhancement by molecular marker assisted selection in wheat breeding.